The Electrophoretic Contribution to the Solutions of Taxonomical Problems of Some Lathyrus L. Taxa Growing in Turkey - Emre, I; Genc, H.; Sahin, A. (Agricultural Research Communication Centre, 2021)
Background: The seed proteins are used as molecular markers to clarify the systematic problems. Also, electrophoretic techniques are safe tools to identify the seed proteins. In present study, it was used the SDS-PAGE technique to solve the taxonomical problems of eight taxa of genus Lathyrus belong to three sections Orobus, Lathyrostylis and Pratensis according to the globulin B and glutelin. Methods: The seed materials were collected from natural habitats and 0.5 g seed were homogenized and centrifuged based on extraction procedure. In addition, the amounts of seed storage protein subfractions were determined by using protein assay. The electrophoretic analysis were performed according to the 12% SDS-PAGE. The gel documentation system (Bio-Rad, USA) was used to analyse the electrophoretic data and UPGAMA was used to construct the dendogram to show the relationships among the species under focus. Results: Current study showed that the species of section Pratensis were different from species of sections Orobus and Lathyrostylis. The differences among the studied taxa shown clearly and all studied taxa were choosen from the protein patterns.. Furthermore, present study demonstrated that L. nivalis has the highest globulin B and glutelin. Results of the present study generally supported the morphological data.
Keywords: Cluster analysis; Electrophoresis; Lathyrus; Seed storage proteins